Accounting, auditing and governance for takaful operations - Htay, Sheila Nu Nu (Wiley finance, 2013)
A comprehensive guide to current issues and practices in governance for Takaful and re-Takaful operations As the global demand for Islamic insurance products increases, a thorough understanding of Takaful principles is vital for accountants, auditors, and leaders of companies offering these products.